Sun-Protective Behaviors of Student Spectators at Inter-school Swimming Carnivals in a Tropical Region Experiencing High Ambient Solar Ultraviolet Radiation - Turner, Denise; Harrison, Simone Lee; Bates, Nicole (Frontiers in Public Health, 2016)
Skin cancer is the most common cancer in humans and Australia (particularly in Queensland) has the highest incidence globally. Sunlight is a known skin carcinogen and reflects off water, exacerbating the risk of sunburn. In 1988, the “SunSmart Program” was developed to promote sun-protection to Australian children. Within a decade, it evolved to include a voluntary national accreditation program for schools, known as the SunSmart Schools (SSS) Program. Additionally, in 2008, it became compulsory for primary schoolchildren attending Queensland government-funded schools to wear a shirt during all water-based activities, except when competing. We observed the proportion of student spectators from 41 Townsville (latitude 19.3°S) primary schools (65.9% SSS) wearing hats at inter-school swimming carnivals in 2009-2011 and 2015 and the proportion wearing a shirt. Overall, a median of 30.7% student spectators from each school wore a hat (max 46.2% [2009]; min 18% [2015]) and 77.3% wore a shirt (max 95.8% [2009]; min 74.5% [2015]), suggesting that hats are under-utilized. Students from non-government (private) schools were twice as likely as students from government schools to wear a hat (41% vs 18.2% p=0.003). Neither the hat nor the shirt-wearing behaviors of student spectators were significantly influenced by their school’s size (number of students), educational advantage, sun-protection policy score or SunSmart status, indicating that other socio-economic factors, not assessed here, may have influenced the results. Our findings suggest that the mandatory swim-shirt policy introduced in 2008 was very effective, especially initially. However, monitoring and feedback of results to schools may be needed to maintain high levels of compliance in the longer-term. Schoolchildren attending swimming carnivals should not rely on sunscreen or shade alone to protect against direct and reflected-sunlight, and need prompting to put a hat and shirt back on immediately after a race. This responsibility could be delegated to either a parent or a student prefect, if teachers are too busy to encourage and monitor sun-safety compliance among the students in their care.